Taxation of Palm Oil Production Results Using on Regression Model (PT. Menthobi Makmur Sustainable) - Wandha Atmaja Aji; Bagus Nugroho; Toyyibah Toyyibah (Akademi Komunitas Perkebunan Yogyakarta, 2023)
PT Menthobi Makmur Lestari is a growing industrial company in the field of palm oil production. The company is targeting increased palm oil production to forecast capacity plans and manufacturing facilities. One of the prediction methods used is multiple linear regression. The free variables used for prediction are the age of the tree, land area (ha), number of trees, number of vines, and the bound variable is the yield of oil palm production. The results of the correlation test using multiple regression showed a significant correlation of 0.05 or less. Hypothesis testing includes multiple linear regression and correlation using the t test and f test with a significance level of α = 0.05. The value of multiple correlation analysis (R) is 0.947 and the coefficient of determination is 90%. The performance of the multiple regression equation is the accuracy of predictions with an average absolute error percentage (MAPE) of 21%, which is formed from the validation of training and testing data.